Use of spirituotherapy and Rogerian counseling on unwed mothers - Cabanlig, Lina Aguilar 1942-
The study examined the differences in adjustment of twenty-three unwed mothers in Marillac Hills, Alabang from their sixth pregnancy to the second month or so after the birth of the baby. This study sought to determine whether Spirituotherapy can bring about a more positive adjustment in unwed mothers towards their situation in a statistically significant manner as compared to the Rogerian method of counseling. The study hopes to stimulate awareness among counselors of these two methods of counseling fostering the well-being of these critically stressed individuals.